PROBLEMS OF TEACHING THE SPECIALTY LANGUAGE TO STUDENTS OF NON-LINGUISTIC UNIVERSITIES - Ruziyeva Komila Yangiboyevna (Scholars Digest Publishing, 2024)
In this article, we will analyze the problems faced by both students and teachers when teaching the language of the specialty. By the term specialty language, we mean the totality of all linguistic means that are used in the field of communication limited by the specialty in order to ensure mutual understanding of people employed in this field.
Keywords: student – teacher, teaching language, specialty, foreign language, ICT, pedagogic skill.